Development and validation of ICP OES methodologies for the determination of metals in powder milk for in proficiency test applications. Issue 1 (March 2021) - Câmara, V; Araújo, T; Caciano de Sena, R; Osorio, A; Almeida, M
Abstract: The main purpose of this work was the development and validation of methods for measuring the macro and microelements (Ca, Na, Mg, P, Fe, and Zn) in powder milk by inductively coupled plasma optical emission spectrometry (ICP OES). The validated methods were applied for measuring these elements in commercial samples in order to choose a suitable mix sample to prepare a reference material batch and use it for organizing a proficiency test. This comparison will be used to evaluate the performance of national laboratories for measuring the mass fraction of essential elements in powder milk. Samples were digested in a microwave reaction system and the elements were measured using the external calibration approach. The standard uncertainty for the mass fractions of Mg, P, Fe and Zn ranged from 1.2% to 2.8%. The method accuracy was evaluated using certified reference material (SRM 1849a) from the National Institute of Standards and Technology (NIST). The results obtained from the SRM 1849a and the measured values with the proposed methodologies was checked, and the results obtained for Mg, P, Fe, and Zn were considered consistent with the certified values, but not for Ca and Na. In this case, we need to perform additional studies in order to reevaluate these last two methods. After we checked the performance of methods, five commercial samples were chosen to determine the mass fraction of Mg, P, Fe, and Zn. Among these samples, in only one all elements were present at a suitable mass fraction for organizing a proficiency test.